2017
DOI: 10.1371/journal.pone.0173385
|View full text |Cite
|
Sign up to set email alerts
|

Human paraoxonase 1 overexpression in mice stimulates HDL cholesterol efflux and reverse cholesterol transport

Abstract: This study was aimed to investigate the effect of human PON1 overexpression in mice on cholesterol efflux and reverse cholesterol transport. PON1 overexpression in PON1-Tg mice induced a significant 3-fold (p<0.0001) increase in plasma paraoxonase activity and a significant ~30% (p<0.0001) increase in the capacity of HDL to mediate cholesterol efflux from J774 macrophages compared to wild-type mice. It also caused a significant 4-fold increase (p<0.0001) in the capacity of macrophages to transfer cholesterol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The coexistence of PON1 and oxLDL decreases the atherogenicity of plaque by inhibiting the bioactivity of oxidized lipids (Cohen et al 2014), while the upregulation of ABCA1 expression on macrophages stimulates the efflux of cholesterol from these macrophages (Ikhlef et al 2016). An investigation by Ikhlef et al using transgenic mice that over-express human PON1 confirmed the involvement of this HDL-associated protein in the stimulation of RCT (Ikhlef et al 2017). RCT is significantly higher in transgenic mice over-expressing PON1 than in wild-type mice (Ikhlef et al 2017).…”
Section: Pon1 and The Capacity Of Hdl To Mediate Cholesterol Effluxmentioning
confidence: 94%
See 1 more Smart Citation
“…The coexistence of PON1 and oxLDL decreases the atherogenicity of plaque by inhibiting the bioactivity of oxidized lipids (Cohen et al 2014), while the upregulation of ABCA1 expression on macrophages stimulates the efflux of cholesterol from these macrophages (Ikhlef et al 2016). An investigation by Ikhlef et al using transgenic mice that over-express human PON1 confirmed the involvement of this HDL-associated protein in the stimulation of RCT (Ikhlef et al 2017). RCT is significantly higher in transgenic mice over-expressing PON1 than in wild-type mice (Ikhlef et al 2017).…”
Section: Pon1 and The Capacity Of Hdl To Mediate Cholesterol Effluxmentioning
confidence: 94%
“…An investigation by Ikhlef et al using transgenic mice that over-express human PON1 confirmed the involvement of this HDL-associated protein in the stimulation of RCT (Ikhlef et al 2017). RCT is significantly higher in transgenic mice over-expressing PON1 than in wild-type mice (Ikhlef et al 2017). In addition, HDL from PON1-Tg mice have a higher capacity to mediate cholesterol efflux than HDL from wild-type mice (Ikhlef et al 2017).…”
Section: Pon1 and The Capacity Of Hdl To Mediate Cholesterol Effluxmentioning
confidence: 95%
“…Animal studies have also shown a high degree of macrophage oxidative stress in PON1‐knockout mice . Thus, even in the absence of a hyperlipidemic state, PON1 deficiency promotes lipid accumulation and inflammatory and oxidative changes in monocytes/macrophages . However, the correlation of circulating PON1 levels with the severity of liver diseases and short‐term mortality in SAH is not yet documented, and further data regarding the role of PON1 in the management of lipid‐laden macrophages and its functionality have not been investigated in SAH.…”
mentioning
confidence: 99%
“…2 of 18 are inversely correlated with the incidence of cardiovascular disease (CVD), mainly coronary heart disease (CHD) [5][6][7]. However, more recent studies have suggested that the relationship between HDL and CVD markers extends beyond the concentration of HDL alone and that the function of HDL may be more important than HDL concentration in protecting against CVD [8][9][10][11]. HDL possesses a number of atheroprotective functions such as mediation of cholesterol efflux from cholesterol-loaded cells, protection against oxidation and inflammation, and promotion of nitric oxide synthesis [12].…”
mentioning
confidence: 99%